Eigenvalues and eigenfunctions of the anharmonic oscillator V(x, y) = x2y2 - Fernández, Francisco Marcelo (2014)
We obtain sufficiently accurate eigenvalues and eigenfunctions for the anharmonic oscillator with potential V(x, y) = x2 y2 by means of three different methods. Our results strongly suggest that the spectrum of this oscillator is discrete in agreement with early rigorous mathematical proofs and against a recent statement that cast doubts about it